Sosiologi Analysis of Literature in The Novel “Jevgar the of Sheana” By Dita Cahya Ningrum Using the Study of the Sociological Theory of Literature by Alan Swingewood - Novi Talentina Lumban gaol; Vina Merina Br Sianipar; Putri Angelina Sirait; Pebri Peronoka Sinaga; Laudya Chintia Baina Siregar; Yensika Putri Sinurat (Merwinspy Publisher, 2026)
The purpose of this study is to examine the sociologi aspects of literature in the Novel The Jevgar The Story Of Sheana By Dita Cahya Ningrum Type your abstract here The focus of the study is the representation pf social reality, the dynamics of characrer relationships, and the social values and criticism embedded in the text. The research questions include how literary works reflect social conditions, how sosial structures affect character behavior, and what velues are conveyed through the storyline. Content analysis and contextual interpretation ware used to analyse the data by connecting the literary work’s internal components with exterior social relity. The findings demonstrate that the book accurately depicts a range of social stratification, social inequality, cultural constraints, and personal challenges in resolving conflicts. In a complicated social setting, the mail character goes through a process of adaption thet reflects the mutual relationship between people and society. Social dynamics sush as dominance, subordination. solidarity, conflict, and forms of resistance to unfair rules are shown through character interactions. Additionally, the study highlights social values like perseverance, hard work, empathy, responsibility and the significance of social interaction in forming a person’s identity and personality. Strong social criticism of injustice and unfairness in society is also presented in the book. As a result this work serves as a medium for social reflection and meaningful learning thet is pertinent to readers everyday lives in addition to being entertaining